Теоретико-методичні підходи до визначення економічної сутності поняття "капітал підприємства" - Пічугіна, Тетяна Сергіївна; Гукова, Таїсія Василівна (НТУ "ХПІ", 2018)
Розглянуто основні підходи до обґрунтування сутності поняття "капітал підприємства". Сформовано власне визначення категорії "капітал" підприємства як матеріальні, грошові та нематеріальні ресурси, що авансовано у формування активів підприємства, необхідних для здійснення його господарської діяльності в довгостроковій перспективі, з метою отримання доходу та прибутку. Визначено склад взаємопов'язаних і взаємообумовлених внутрішніх і зовнішніх факторів, що впливають на структуру капіталу підприємства та визначають можливості управління ним.

The main approaches to substantiating the essence of the concept of "capital of an enterprise" are considered. The actual definition of the category of "capital" of the enterprise as material, monetary and intangible resources, which was advanced in forming the assets of an enterprise necessary for its economic activity in the long run, was formed for the purpose of obtaining income and profits. The composition of interconnected and mutually determined internal and external factors influencing the structure of the enterprise capital and determine the possibilities of management of it are determined. The internal factors determining the peculiarities of the formation and composition of the capital of enterprises are: the organizational and legal form of the enterprise's activity, the existing capital structure, the level of profitability of the operating acti vity, the size of the enterprise and the stage of its life cycle, the degree of financial stability, the priorities of owners and management in choosing a method of financial provision, etc. External factors are the following: the state of the legislative process, the level of administrative influence on the economy of enterprises, the stability of the commodity market, the financial market situation, the tax burden on the enterprise, the ratio of creditors and investors to a particular enterprise, the degree of credit risk and the level of potential of the banking system, tendencies of development of other branches of economy.
Theoretical and methodological approaches to the determination of the "capital of enterprise" economic essence
Keywords: капітал; фінансові ресурси; підхід; кругообіг; кошти; внутрішні чинники; зовнішні чинники; фінансове забезпечення; capital; financial resources; approach; circulation; funds; internal and external factors; financial security